Blended Learning with Flipped Classroom Strategy : The Effect to the Independence and Learning Outcomes - Tri Mulyati; Basori Basori; Dwi Maryono (Journal of Informatics and Vocational Education, 2022)
In terms of goal planning, procedures, and evaluation of learning results, learning independence refers to an individual's willingness to study on his own initiative, with or without the assistance of others. The flipped classroom is one learning style that can be utilized to improve student independence. This study aims to determine (1) whether there are differences in independence in the application of the Blended Learning strategy Flipped Classroom with the conventional learning model; (2) Are there differences in student learning outcomes in the application of the Blended Learning strategy Flipped Classroom with the conventional learning model (3) Is there an increase in independence in the application of the Blended Learning strategy Flipped Classroom with the conventional learning model; (4) Is there an increase in student learning outcomes in the application of the Blended Learning strategy Flipped Classroom with the conventional learning model. The pretest-posttest control group design model was applied in this study, which used the quasi experimental design method. The participants in this study are students from SMK Negeri 1 Gondang's classes X Multimedia 1 and X Multimedia 2. A total of 70 pupils were used in the study. Total sampling was employed as the sampling method. Pretests, posttests, and questionnaires are used to collect data. Balance tests, normality testing, homogeneity tests, and hypothesis tests are among the data analysis procedures employed. The findings revealed that the Blended Learning learning model combined with the flipped classroom method had an impact on student independence and learning outcomes.